ON ASSESSING EMOTIONAL INTELLIGENCE AS A PRECURSOR OF POSITIVE PERSONALITY FUNCTIONING AND MENTAL HEALTH - Chetveryk-Burchak, Alina; Nosenko, Eleonora (Advances in Social Sciences Research Journal, 2014)
The recent conceptualization of emotional intelligence (EI) as a new dynamic integral trait (Austin et al., 2008; Ziedner et al., 2009) and “a wise management of emotions” (Nosenko, 2011) has opened up prospects for the comprehensive assessment of its role in positive personality functioning. The objective of this paper is to present empirical findings (obtained on a sample of 135 participants) which show that the individuals with high levels of EI are characterized by positive behavioral outcomes, indicative of their mental health continuum (Keyes, 2002) and achievements in the fulfillment of the basic life tasks (Janakov, 2008). The findings are claimed to help solving the controversy of the ability/trait conceptualization of EI.